UPAYA PENINGKATAN KOMPETENSI MAHASISWA MELALUI PEMBELAJARAN BERKARAKTER DENGAN PENDEKATAN INQUIRY BERBANTUAN CABRI 3D PADA GEOMETRI RUANG - Venissa Dian Mawarsari; Achmad Solichan (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The purpose of this research is to improve student’s competency (student’s learning achievement) using character-based lesson plan with inquiry approach with Cabri 3D on space geometry subject. The research is a quantitative eperiment by comparing the process before and after the use of the lesson plan. Test, observation, and documentation ware used in the research to support the result. It showed the average pre test result 31,94 and for post test was 85,17. Based on the statistical analysis using paired sample t test, t counted 25,18 and indicated significant improve on the student’s competency. However, the application of character-based lesson plan with inquiry approach with Cabri 3D give significant improvement on space geometry subject.Keywords: character-based lesson plan, inquiry, cabri 3D.